PREDICTION OF FINANCIAL DISTRESS IN PROPERTY AND REAL ESTATE COMPANIES IN INDONESIA: LIQUIDITY RATIO, LEVERAGE RATIO, ACTIVITY RATIO, PROFITABILITY RATIO, GROWTH RATIO - Purwanti, Desy; Ulan Sari, Riski (ZILLZELL MEDIA PRIMA, 2023)
This study aimed to examine the effect of the ratio liquidity, leverage, activity, profitability and growth on the probability of financial distress. Liquidity is measured by quick ratio, leverage is measured by debt ratio, activity is measured by total asset turn over, profitability is measured by gross profit margin and growth is measured by net profit growth. The population in this study are all property and real estate company listed on the Indonesia Stock Exchange in 2014 until 2016. The total samples tested were 41 company selected by purposive sampling technique. This research analyzes financial distress through company annual report by using content analysis method. Data analysis techniques use panel data regression with EViews 9.0 program. These results indicate that the ratio of activity and profitability affect the financial distress. While the ratio of liquidity, leverage and growth don’t affect the financial distress.